The sustainability of communication of behavioral imp act (combi) program in preventing and controlling dengue fever in Kampung Batang Merbau, Tanah Merah, Kelantan - Abdullah Busam, A. Shukor (2010)
Introduction: Dengue fever is one of the most important arthropod-borne viral diseases. No doubt that the COMB! program has shown its impact in reducing the prevalence of dengue fever in the affected community. However, the sustainability of the program is still questionable in ensuring the area remains free from the dengue outbreak. Objective: To evaluate the sustainability of COMBI program towards prevention and control of dengue fever in Kampung Batang Merbau, Tanah Merah, Kelantan. Methods: This study utilized a community intervention design. Residents of Kampung Batang Merbau were taken as the subjects. Sample size was determined by comparing the means between two groups of populations which were paired. A self-guided questionnaire was used. Ethical clearance was obtained prior to the start of the study. The comparison data, which was carried out prior to the start of COMB I program, was obtained from the District Health Office of Tanah Merah. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 12. Results: One hundred and fifty residents participated in this study. The mean score of knowledge and practice were higher post COMB I program. Mean score of practice and understanding score of COMB! program was positively, directly, linearly and weakly correlated (p = 0.016, r = 0.197). No significant association between sociodemographic factors and understanding score of COMB I program. Conclusion: COMB! program was well sustained in preventing and controlling dengue outbreak in Kampung Batang Merbau up to eighteen months after the withdrawal of external support from Ministry of Health Malaysia.